2012
DOI: 10.1016/j.mrrev.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing mutagenic mode of action determinations of regulatory and advisory agencies

Abstract: The determination of whether a chemical induces cancer through a mutagenic or genotoxic mechanism frequently plays an important role in evaluating the risks associated with low dose exposure. Although various approaches are employed for making mode of action decisions, a systematic investigation to identify the major factors that influence these determinations has not been performed. To accomplish this, over 40 chemical risk assessments conducted by U.S. or international regulatory agencies and organizations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 68 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…In addition to genotoxicity test results, other factors should be considered in making a determination of whether or not a chemical acts through a mutagenic mode of action. As described in Eastmond [], these include “the chemical properties of the agent, its metabolites and degradation products; its metabolism and toxicokinetics;… structural or metabolic similarities to known mutagenic or nonmutagenic chemicals; characteristics of the tumors induced in the animal bioassays; and the origin of the observed effects. The quality of the data, the specific genotoxic endpoint and its sensitivity to assay conditions and toxicity were also important considerations….…”
Section: Evaluation Of Genotoxicity Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to genotoxicity test results, other factors should be considered in making a determination of whether or not a chemical acts through a mutagenic mode of action. As described in Eastmond [], these include “the chemical properties of the agent, its metabolites and degradation products; its metabolism and toxicokinetics;… structural or metabolic similarities to known mutagenic or nonmutagenic chemicals; characteristics of the tumors induced in the animal bioassays; and the origin of the observed effects. The quality of the data, the specific genotoxic endpoint and its sensitivity to assay conditions and toxicity were also important considerations….…”
Section: Evaluation Of Genotoxicity Test Resultsmentioning
confidence: 99%
“…In addition to genotoxicity test results, other factors should be considered in making a determination of whether or not a chemical acts through a mutagenic mode of action. As described in Eastmond [2012], these include "the chemical properties of the agent, its metabolites and degradation products; its metabolism and toxicokinetics;. .…”
Section: Evaluation Of Complex Genotoxicity Test Datamentioning
confidence: 99%
“…Some regulatory authorities have concluded that captan, folpet, and Cr(VI) induce intestinal tumors in mice via chronic mucosal toxicity and regenerative hyperplasia ( U.S. EPA 2004 ; Eastmond 2012 ; IPCS 1995 ; HealthCanada 2015 ; TCEQ 2016 ). These MOA determinations were based on multifaceted research efforts conducted for each agent ( Cohen et al 2010 ; Gordon 2007 ; Thompson et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Like Cr(VI), neither captan nor folpet induces intestinal tumors in rats ( Cohen et al 2010 ; Gordon 2007 ). Despite evidence for in vitro genotoxicity, both captan and folpet are not genotoxic in vivo and appear to increase tumor risk in mice due to chronic mucosal wounding and regenerative hyperplasia ( Cohen et al 2010 ; Gordon 2007 ; Arce et al 2010 ), and regulators have determined that these organochloride compounds induce intestinal tumors via nonmutagenic (i.e., threshold) mechanisms ( United States Environmental Protection Agency [U.S. EPA] 2004 ; Eastmond 2012 ; International Programme for Chemical Safety (IPCS) 1995 ), in which chemically induced villous cytotoxicity and resulting crypt regenerative hyperplasia are nonneoplastic precursors that increase the chance of intestinal carcinogenesis. More recently, some scientists have concluded that Cr(VI) induces intestinal tumors through similar mechanisms ( Haney 2015 ; HealthCanada 2015 ; TCEQ 2016 ; Thompson et al 2013 , 2014 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Critical involvement of non-DNA targets Aneuploidy: benomyl; carbendazim [9][10][11] [14,19] Species and tumor-specific non-genotoxic mode of action Induction of thyroid follicular cell tumors by inorganic chlorates [20] In order to establish exposure limits that minimize human risk of organ toxicity or carcinogenicity, PoD values from animal models in conjunction with uncertainty factors are used (e.g. [33][34][35][36][37][38]).…”
Section: Mechanistic Information Example(s) Referencesmentioning
confidence: 99%